A Psychoanalytic Reading of Abdulrazak Gurnah’s Gravel Heart - Al Areqih, Rashad (LPPM Universitas Advent Indonesia, 2022)
Abstract Psychoanalytic criticism probes deeply into human behavior, uncovering unconscious anxieties, desires, and problems. This study examines Abdulrazak Gurnah’s Gravel Heart (2017) from a psychanalytic perspective, highlighting Salim’s different stages of life and tracing the troubles he encounters. Psychoanalytic theory is applied to the concepts of family and early childhood experiences, as well as defense mechanisms: fear of abandonment, social shame and inferiority, low self-esteem, avoidance, fear of intimacy, and death and loss. The theme of death and loss becomes a hallmark of Salim’s mysterious family, which is full of secrets. Despite Salim’s accomplishments as a teenager, he finds himself occupied by his family conflicts. Later, he accepts his uncle Amir’s invitation to move to the United Kingdom (UK) to attend college. This study found that Salim’s traumatic experiences at an early age influenced his future choices and behaviors, particularly when he moved to the UK and met friends of different races from all over the world, each with their own story, which was definitely varied from his own. Eventually, Salim became overwhelmed by feelings of social inferiority, loss, and failure because he could not change his fate to a more brilliant future. The mysteries he spent his life attempting to solve, ultimately about his father, uncovered that his alienation and isolation was because of the dishonor his mother brought to the family to save her brother, Amir, from jail. However, his father’s story was revealed too late to heal Salim’s past trauma.